Overview of Foreign Investment Policy in India - Agarwal, B. K (Journal of Commerce and Trade, 2015)
Foreign investment refers to the investments made by the residents of a country in the financial assets and production process of another country. The foreign investment is necessary for all developing nation as well as developed nation but it may differ from country to country. The developing economies are in a most need of these foreign investments for boosting up the entire development of the nation in productivity of the labour, machinery etc. The foreign investment or foreign capital helps to build up the foreign exchange reserves needed to meet trade deficit or we can say that foreign investment provides a channel through which developing countries gain access to foreign capital which is needed most for the development of the nations in the area of industry, telecom, agriculture, Information Technology etc. The foreign investment also affects on the recipient country like it affects on its factor productivity as well as affects on balance of payments. Foreign investment can come in two forms: foreign direct investment and foreign institutional investment.